Hubungan Motivasi Belajar Dengan Regulasi Diri Dalam Belajar Siswa Pasca Pandemi Covid 19 Pada Mata Pelajaran Biologi - Mohammad Tarmizi; Jamilah, Jamilah; Eka Damayanti (Al-AHYA: Jurnal Pendidikan Biologi, 2025)
This study aims to describe learning motivation, self-regulation in learning and to analyze the relationship between learning motivation and self-regulation in student learning after the covid 19 pandemic in class XI Madrasah Aliyah Madani Alauddin. This type of research is ex post facto research. The population in this study were all students of class XI MIA Madrasah Aliyah Madani Alauddin in the even semester of the 2020/2021 academic year, a total of 121 people. The sample in this research class XI MIA 2 is 38 students. The sampling technique used in this research is Systematic Random Sampling. Methods of data collection is done by using a questionnaire. The research instrument used was a learning motivation questionnaire with self-regulation in learning. Data analysis used is descriptive and inferential analysis. The results of the analysis were obtained: 1) Post-pandemic Covid-19 student learning motivation was in the moderate category with a total of 21 students (55.3%). 2) Self-regulation in student learning after the Covid-19 pandemic is in the moderate category with a total of 26 (68.4%). 3) There is a significant relationship between learning motivation and self-regulation in student learning after the covid pandemic in class XI MIA Madrasah Aliyah Madani Alauddin because Sig 0.000 <0.05 and r count > r table, namely (0.570) > (0.320).